2014
DOI: 10.1016/j.tjog.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic actinomycosis with abundant ascites, pleural effusion, and lymphadenopathy diagnosed with endometrial biopsy and treated with medication only

Abstract: Pelvic actinomycosis should always be considered in patients with a pelvic mass and peritoneal infiltration, especially in the presence of intrauterine device use, despite the fact that abundant ascites, pleural effusion, and lymphadenopathy almost never accompany pelvic actinomycosis. Endometrial/endocervical biopsy may yield a diagnosis without an invasive procedure and should be performed. Because of the excellent response to penicillin, medical treatment alone is an effective method to eradicate pelvic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This result was in line with a case described of PA extended to the serosa and to the lombo-aortic lymphatic chain. After a pre-treatment diagnosis, the patient was successfully treated with antibiotics exclusively for 6 months (10 million IU/ day of penicillin G IV for 2 weeks, then amoxicillin PO 500 mg × 3/d), without recourse to surgery [34]. Previous studies have reported the need for prolonged antibiotic treatment at high doses because of the seriousness of the infection and a significant tissue fibrosis (penicillin: 2 to 6 weeks IV to continue for 6 to 12 months by oral route).…”
Section: Discussionmentioning
confidence: 99%
“…This result was in line with a case described of PA extended to the serosa and to the lombo-aortic lymphatic chain. After a pre-treatment diagnosis, the patient was successfully treated with antibiotics exclusively for 6 months (10 million IU/ day of penicillin G IV for 2 weeks, then amoxicillin PO 500 mg × 3/d), without recourse to surgery [34]. Previous studies have reported the need for prolonged antibiotic treatment at high doses because of the seriousness of the infection and a significant tissue fibrosis (penicillin: 2 to 6 weeks IV to continue for 6 to 12 months by oral route).…”
Section: Discussionmentioning
confidence: 99%
“…Further evaluation by removal of IUD and pap smear collection can also support the diagnosis. Pap smear is a simple diagnostic aid of greater sensitivity than vaginal cultures, with accuracy of up to 69% [6]. Once diagnosis is confirmed, exclusive medical management with long term use of antibiotics and close follow-up is an acceptable approach which could prevent the need for extensive and risky surgical interventions in patients with pelvic actinomycosis.…”
Section: Discussionmentioning
confidence: 99%
“…The infection is characterized by suppurative and granulomatous inflammation, contiguous spread, and the formation of colonies described macroscopically as sulfur granules [2, 3, 6]. It can become pathogenic when mucosal integrity is compromised or in the presence of a foreign body, like an IUD [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Actinomyces and Nocardia infections are rarely associated with body cavity effusions (ie, thoracic, pericardial, peritoneal) . Typically, these effusions present secondary to associated mass lesions or pseudotumors.…”
Section: Cytopathology Of Nocardia and Actinomyces On Exfoliative Spementioning
confidence: 99%